Incidence of Trichodina heterodentata from Clarias gariepinus in two fish farms in Calabar, Cross River State, Nigeria. - Eyo, Victor Oscar; Xavier, Usanga Jerome; Udobong, Bridget Effiong (Journal of Aquatic Sciences, Association for Aquatic Sciences of Nigeria, 2018)
The study was conducted to determine the prevalence, mean intensity, and abundance of Trichodina heterodentata in Clarias gariepinus from two selected fish farms in Calabar.. A total of eighty (80) samples of C. gariepinus from the two farms (40 each) were necropsied for parasitological analysis. Gill, skin and fin biopsies were prepared from each specimen following standard methods. Parasitological indices including prevalence, mean intensity and abundance were calculated according to standard formulae. Results obtained showed that 18 fish samples were infested with T. heterodentata from the two farms with a total of 84 T. heterodentata parasites. In farm 1, prevalence (20.0), intensity (4.50) and abundance (0.90) of Trichodina parasite was lower than farm 2 with prevalence (25.0), intensity (4.80) and abundance (1.20). In both farms, prevalence, intensity and abundance of T. heterodentata were higher in female C. gariepinus than male but not significant (p>0.05). Clinical signs observed in the two farms were loss of appetite, necrosis and skin ulcer, sluggish movement and excessive secretion from the gills. Trichodina infestation in farmed fish may lead to poor growth rates and high mortality which will subsequently result in huge monetary loss and low profit margin by increasing production cost due to the cost of treatments. It is therefore concluded that ponds or tanks should be properly disinfected before stocking of healthy fingerlings.
Keywords: Keywords: Prevalence; Intensity; Abundance; Trichodina heterodentata; Clarias gariepinus